2018
DOI: 10.1088/1361-648x/aac188
|View full text |Cite
|
Sign up to set email alerts
|

Bond compressibility and bond Grüneisen parameters of CdTe

Abstract: Extended x-ray absorption fine structure (EXAFS) at the Cd K edge and diffraction patterns have been measured on CdTe as a function of pressure from 100 kPa (1 bar) to 5 GPa using a cell with nano-polycrystalline diamond anvils and an x-ray focussing scanning spectrometer. Three phases-zincblende (ZB), mixed cinnabar-ZB and rocksalt (RS)-are well distinguished in different pressure intervals. The bond compressibility measured by EXAFS in the ZB phase is slightly smaller than the one measured by diffraction and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 79 publications
(162 reference statements)
1
10
0
Order By: Relevance
“…Such a kind of phenomenon cannot be evaluated by long-range Bragg scattering-based techniques, as the case of X-ray and neutron diffraction. Instead, EXAFS can also probe structural and vibrational disorders of individual pair-bonds, being capable of distinguishing an anharmonic contribution as a function of pressure 30 and temperature. 31 Indeed, XAS was already used to characterize the local features of skutterudites, such as the case of RFe 4 Sb 12 (R = K, Na, Ca, Sr, and Ba), 32 LT 4 X 12 (L = Ce, Eu, Yb; T = Fe, Ru; X = P, Sb), 33 and Ba x In y Co 4 Sb 12 , 34 with success.…”
Section: Introductionmentioning
confidence: 99%
“…Such a kind of phenomenon cannot be evaluated by long-range Bragg scattering-based techniques, as the case of X-ray and neutron diffraction. Instead, EXAFS can also probe structural and vibrational disorders of individual pair-bonds, being capable of distinguishing an anharmonic contribution as a function of pressure 30 and temperature. 31 Indeed, XAS was already used to characterize the local features of skutterudites, such as the case of RFe 4 Sb 12 (R = K, Na, Ca, Sr, and Ba), 32 LT 4 X 12 (L = Ce, Eu, Yb; T = Fe, Ru; X = P, Sb), 33 and Ba x In y Co 4 Sb 12 , 34 with success.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Moreover, temperature dependent EXAFS analysis provides local thermodynamical information on the Debye-Waller factors (mean square relative displacements) and thermal expansion, and a lot of EXAFS works have been performed to develop the EXAFS methodology and clarify interesting structural and thermodynamical properties. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] For instance, in the study on the FeNi Invar alloy, 6 it was found that the interatomic distances and thermal expansion around Fe and Ni are meaningfully different from each other, although the X-ray diffraction looks as if the alloy formed perfect fcc lattice. On the other hand, from the theoretical point of view, the path-integral effective classical potential method (PIECP) [6][7][8][9][28][29][30][31][32][33] is regarded as one of the most appropriate methods to investigate the interatomic distance, the mean square relative displacements, and thermal expansion including the quantum fluctuation, which is essentially important to describe the harmonic and anharmonic thermal properties at low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are some publications dealing with the EXAFS edges of the anion, with the work being confined to bromine, we want to limit ourselves to the Pb L3-edge for better comparability. Besides the consideration of the temperature dependence of the EXAFS Debye–Waller factor, the framework of the temperature-dependent EXAFS cumulant analysis developed in the last decades allows further statements about the properties of the investigated atomic pairs since statements about the anharmonicity can also be made …”
Section: Introductionmentioning
confidence: 99%